The Micro Impact of Macroprudential Policies : Firm-Level Evidence - Ayyagari, Meghana (IMF Working Papers; Working Paper ;, 2018)
Combining balance sheet data on 900,000 firms from 48 countries with information on the adoption of macroprudential policies during 2003-2011, we find that these policies are associated with lower credit growth. These effects are especially significant for micro, small and medium enterprises (MSMEs) and young firms that, according to the literature, are more financially constrained and bank dependent. Among MSMEs and young firms, those with weaker balance sheets exhibit lower credit growth in conjunction with the adoption of macroprudential policies, suggesting that these policies can enhance financial stability. Finally, our results show that macroprudential policies have real effects, as they are associated with lower investment and sales growth.